Fiber-reinforced fixation implant for proximal interphalangeal joint arthrodesis shows advanced implant bio-integration at 2-year follow-up. Issue 8 (December 2022) - Štalc, Jurij; Cicchinelli, Luke D.; Miller, Stuart; Sofka, Carolyn M.; Richter, Martinus
Abstract: Background: A bio-integrative fiber-reinforced implant (OSSIOfiber® Hammertoe Fixation Implant, OSSIO Ltd., Caesarea, Israel) for proximal interphalangeal joint (PIPJ) correction-arthrodesis showed partial bio-integration at 1-year follow-up (1FU) in a previous study. The study was prolonged to assess the bio-integration at 2-year-follow-up (2FU). Methods: Twenty-four patients with proximal interphalangeal joint (PIPJ) correction-arthrodesis using the fiber-reinforced implant and analysed at 1FU, completed 2FU. Follow-up included clinical examination, patient reported outcomes, radiographs, MRI and bio-integration scoring. Results were compared between the 1FU and 2FU (paired t-test). Results: Radiographs confirmed fusion in 96 % (n = 23) at 2FU (1FU, 92 % (n = 22)). Implant was no longer visible in 21 % (n = 5), partially visible in 33 % (n = 8), and fully visible in 46 % (n = 11)(1FU, fully visible 100 % (n = 24)). The border between implant and surrounding bone was scored not visible in 88 % (n = 21) and partially visible in 12 % (n = 3) (1FU, border partially visible 100 % (n = 24)). There were no cyst formation or fluid accumulation findings 1FU/2FU. Mild bone edema was detected in 4 % (n = 1) (1FU, 29 % (n = 7)). None of the edema findings were considered as adverse implant related. The mean bio-integration score was 9.71 ± 0.69 at 2FU (1FU, 7.71 ± 0.46). The parameters of border between implant and bone and bone edema further improved at the 2FU compared to the 1FU, total bio-integration score was also higher at 2FU than 1FU (each p < 0.05). Conclusions: This study demonstrates 96 % PIPJ fusion rate and increased bio-integration from 1FU to 2FU, reaching advanced bio-integration of the fiber-reinforced implant at 2FU.